Proximity of uterosacral ligament suspension sutures and S3 sacral nerve to pelvic landmarks. (January 2017) - Maldonado, Pedro; Stuparich, Mallory; McIntire, Donald; Wai, Clifford
Abstract Introduction and hypothesis To describe the relationships between pelvic bony landmarks to points along the third sacral nerve and to uterosacral ligament suspension sutures. Methods Three transvaginal uterosacral ligament suspension sutures were placed bilaterally in unembalmed female human cadavers. The third sacral nerve was marked at the foramen (S3a) and at two additional points at 1-cm intervals along its course caudally (S3b, S3c). Three bony pelvic landmarks were identified and marked, including the ischial spine, pubic symphysis, and coccyx. Distances from each landmark to each suture and nerve point were measured. The distance from each landmark to each S3 nerve point was extended radially, encompassing an arbitrary zone in which sutures may be placed and thus where nerve injury may occur. Zones of potential nerve injury included: zone A (closest to the sacral nerve root), zone B, and zone C (closest to the landmark). Descriptive statistics were used and comparisons were made using Student'st test and ANOVA. Results Ten cadaver specimens were dissected. For the ischial spine, the distances to points S3a, S3b, and S3c were 6.3, 5.4, and 4.6 cm respectively. Approximately two thirds of the sutures were noted beyond zone C, indicating a potentially increased risk of nerve injury with suture placement in zones farthest from the ischial spine given their proximity to the sacral nerve. Conclusions Using the ischial spine as a landmark, increased sacral nerve injury could result from suture placement beyond the mean distance of 4.6 cm from the ischial spine. The use of bony landmarks in avoiding sacral nerve injury may be as important as suture depth and angle of suture placement.